Konsep Hak Asasi Manusia (HAM) dalam Perspektif Syariat Islam - Noor, M. Sholihin (Fakultas Adab dan Humaniora, UIN Syarif Hidayatullah Jakarta, Indonesia, 2007)
Human being is a God's creation (the Al mighty) that has basic right called human basic right to guarantee the existence of their values and prestiges and environment harmonization. The God also gives human being the freedom to manage and to take care the entire world responsibly in order to get the prosperity. Therefore, there are a forbidden of discrimination based on sex, race, and religion. Eventhough, this is not noticed by shariat, but international convension had admitted as a part of basichuman right.